Pengembangan Media Pembelajaran Tematik Game Menjelajah Ruang Berbasis Construct untuk Meningkatkan Kemampuan Berpikir Kritis dan Pemecahan Masalah Bagi Siswa di Sekolah Dasar - Nova Aria Siswi; Wahyudi Wahyudi (Peneliti.net, 2021)
The purpose of this study was to determine the effectiveness of the thematic learning media Construct-based Space Exploration Game to improve students' critical thinking skills with thematic-based problem solving in elementary schools. This research is a type of development research or R&D (Research and Development). Development research is the process used to develop and validate Educational products. The results showed that the game media exploring space in the thematic learning of grade 4 students was practical for use in learning. This can be shown from the questionnaire on the response results of grade 4 students. The results of the student response questionnaire obtained a score of 219, with a percentage of 91% which can be categorized as very good.